2010
DOI: 10.1111/j.1744-313x.2010.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

TNF microsatellite alleles may confer protection against the development of lipodystrophy syndrome in Brazilian HIV patients

Abstract: The aim of this study was to evaluate the frequency of TNFa-e microsatellites and the promoter region (TNF-308 and TNF-238) in HIV/AIDS-infected patients presenting or not lipodystrophy syndrome (LS). The design is the genetic case-control association study. Microsatellite and the TNF promoter region polymorphisms were amplified by PCR and submitted to polyacrylamide gel electrophoresis. The genotypes and allele frequencies for 67 HIV-positive patients with lipodystrophy were compared with 50 HIV-positive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Previous studies reported that the TNF − 308 G allele and −308GG genotype were associated with susceptibility to LS in the Brazilian population. The TNF‐α − 238G/A polymorphism was found to be associated with LD in the Australian population 61,62 . The TNF‐α −238G/−308G haplotype showed protection against developing LS syndrome 61 .…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies reported that the TNF − 308 G allele and −308GG genotype were associated with susceptibility to LS in the Brazilian population. The TNF‐α − 238G/A polymorphism was found to be associated with LD in the Australian population 61,62 . The TNF‐α −238G/−308G haplotype showed protection against developing LS syndrome 61 .…”
Section: Methodsmentioning
confidence: 95%
“…The TNF-α À 238G/A polymorphism was found to be associated with LD in the Australian population. 61,62 The TNF-α À238G/À308G haplotype showed protection against developing LS syndrome. 61 The occurrence of the TNF-α 238G/A polymorphism was approximately twice as high in individuals suffering from LD in comparison with those persons without LD in the Indian population.…”
Section: Genetic Variation Of Cytokine Genes and Hivldmentioning
confidence: 98%
See 1 more Smart Citation
“…High concentration of TNF-α may influence HIV replication via clonal expansion of infected T lymphocytes. In addition, TNF-α induces rapid apoptosis of bystander T helper cells, thereby accelerating the rate of T-cell depletion in HIV disease [8]. Several functional SNPs have been identified within the TNF-α gene cluster, the most widely studied of which are: G>A transition at position -238, G>A transition at position -308, and C>A transversion at position -863 [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Esses polimorfismos são marcados pela substituição de G por A nas duas posições. A presença do alelo A na posição -308 está relacionada com o aumento da transcrição do TNF (KROEGER; CARVILLE; ABRAHAM, 1997).Existem várias pesquisas de associação dos polimorfismos dessas citocinas na infecção tanto pelo HIV quanto pelo HCV(BOUZGARROU et al, 2011;CASTELAR et al, 2010;SILVA et al, 2010). Entretanto, na literatura indexada, não foram identificados estudos que tipificaram e compararam os polimorfismos do TNF-Identificar os sinais e sintomas relacionados às reações adversas do tratamento da hepatite C, fornecendo subsídios para a elaboração de um plano sistematizado de assistência de enfermagem aos pacientes portadores da coinfecção HIV/HCV.Conforme solicitado ao CEP, houve dispensa da apresentação do Termo de Consentimento Livre e Esclarecido (TCLE) aos participantes não encontrados, visto que no estudo foram utilizadas amostras biológicas previamente armazenadas, colhidas de muitos pacientes que evoluíram ao óbito devido ao agravamento de suas condições de saúde.…”
unclassified